2054. Physician Responses to Positive Rapid Diagnostic Tests for Candida Fungemia in the Absence of Concomitant Positive Blood Cultures. (26th November 2018) - Bhowmick, Tanaya; Jones, Laura; Kirn, Thomas; Narayanan, Navaneeth; Weinstein, Melvin
Abstract: Background: Candida species are the fourth leading cause of nosocomial bloodstream infections in the United States. Unfortunately, detection, identification and susceptibility testing using standard instrumented blood culture systems and routine microbiological techniques may take 4–10 days. Moreover, sensitivity of routine blood cultures for candidemia is only 50 to 75%. The T2 Candida Panel (T2CP) is an FDA-approved assay that rapidly detects the presence of five Candida species directly from whole blood in 3–5 hours. We examined mortality and antifungal therapy (AFT) decisions based on positive (pos) results of a T2CP in patients with negative (neg) blood cultures. Methods: We performed a case series of all patients who had a pos T2CP with concomitant neg blood cultures at our institution from March 1, 2016 to March 1, 2018. If a patient had multiple valid T2CP, only the first pos result was used for analysis. Medical records were reviewed for demographics, comorbidities, risk factors for candida infection, length of stay, use and duration of AFT, and 14-day and in-hospital mortality from the time of the T2CP. Results: Fifteen patients were identified who met inclusion criteria. Eight patients were immunocompromised: four (26.7%) solid cancer malignancy, three (20%) hematologic malignancy, and one kidney transplant recipient. Pos T2CP results by species were as follows: 53.3% C. albicans / C. tropicalis, 40% C. parapsilosis, and 6.7% C. glabrata / C. krusei . Median SOFA, Charlson comorbidity index, and Candida scores were 6, 6, and 9, respectively. Fourteen-day mortality was 40% and in-hospital mortality was 53.3%. Only two patients were on prophylactic AFT due to an underlying hematologic malignancy at the time of T2CP; in both cases, azole AFT was replaced with an echinocandin in response to the pos T2CP. Of the remaining 13 patients who were not on prophylactic AFT, all were started on AFT after pos T2CP result. Conclusion: Physicians escalated or initiated AFT therapy based on pos T2CP in severely ill patients who had negative blood cultures. Unfortunately, the population had high severity index scores and high mortality despite initiation or escalation of AFT. We hypothesize that earlier testing and detection of Candida fungemia may lead to faster initiation of AFT and better outcomes. Disclosures: All authors: No reported disclosures.